2017
DOI: 10.1536/ihj.16-364
|View full text |Cite
|
Sign up to set email alerts
|

The Shortest QRS Duration of an Electrocardiogram Might Be an Optimal Electrocardiographic Predictor for Response to Cardiac Resynchronization Therapy

Abstract: SummaryQRS duration has been associated with the response to cardiac resynchronization therapy (CRT). However, the methods for defining QRS duration to predict the outcome of CRT have discrepancies in previous reports. The aim of this study was to determine an optimal measurement of QRS duration to predict the response to CRT.Sixty-one patients who received CRT were analyzed. All patients had class III-IV heart failure, left ventricular ejection fraction not more than 35%, and complete left bundle branch block… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…23,24) However, patients with baseline QRS duration "150 ms showed narrowed QRS duration following biventricular pacing, with significantly improved cardiac functions. [25][26][27] In patients with third-degree AVB, pacing QRS duration was not associated with the location of the conduction block 28) but was correlated with baseline QRS duration. 28,29) In this study, patients with QRS duration < 120 ms showed significantly widened QRS duration after biventricular pacing, with poor response to CRT, while patients with QRS duration "150 ms had remarkably shortened QRS duration following biventricular pacing, with a response rate to CRT as high as 76.5%.…”
Section: Discussionmentioning
confidence: 97%
“…23,24) However, patients with baseline QRS duration "150 ms showed narrowed QRS duration following biventricular pacing, with significantly improved cardiac functions. [25][26][27] In patients with third-degree AVB, pacing QRS duration was not associated with the location of the conduction block 28) but was correlated with baseline QRS duration. 28,29) In this study, patients with QRS duration < 120 ms showed significantly widened QRS duration after biventricular pacing, with poor response to CRT, while patients with QRS duration "150 ms had remarkably shortened QRS duration following biventricular pacing, with a response rate to CRT as high as 76.5%.…”
Section: Discussionmentioning
confidence: 97%